Existential Transformational Game Design: Harnessing the “Psychomagic” of Symbolic Enactment - Rusch, Doris C.; Phelps, Andrew M. (Frontiers in Psychology, 2020)
This paper explores indexical symbolic enactment as a way to promote authenticity and inner balance through digital games. Drawing on research from cognitive anthropology, neurobiology, and psychology, the following presents an argument for why and how indexical symbolic enactment can impact us on a deep, unconscious level and contribute to personal transformation. It identifies four high-level guidelines that can inform existential transformative game design: (1) ritual theming (i.e., liberation, transformation, and commemoration/celebration); (2) metaphorical approach; (3) contextual mechanisms that promote a readiness for change and processing; and (4) psychological resonance. It then uses these guidelines as an analytical lens for a case study on the game Papo & Yo (Minority Media Inc., 2012). This analysis shows how indexical symbolic enactment can contribute to a game’s transformative potential and examines missed opportunities when design decisions emphasize gameplay considerations rather than symbolic congruency and psychological resonance.